4-epi-Isofagomine derivatives as pharmacological chaperones for the treatment of lysosomal diseases linked to β-galactosidase mutations: Improved synthesis and biological investigations. Issue 20 (1st November 2018) - Front, Sophie; Almeida, Sofia; Zoete, Vincent; Charollais-Thoenig, Julie; Gallienne, Estelle; Marmy, Céline; Pilloud, Vincent; Marti, Roger; Wood, Tim; Martin, Olivier R.; Demotz, Stéphane
Graphical abstract: Abstract: (5a R )-5a- C -pentyl-4- epi -isofagomine1 is a powerful inhibitor of lysosomal β-galactosidase and a remarkable chaperone for mutations associated with GM1-gangliosidosis and Morquio disease type B. We report herein an improved synthesis of this compound and analogs (5a- C -methyl, pentyl, nonyl and phenylethyl derivatives), and a crystal structure of a synthetic intermediate that confirms its configuration resulting from the addition of a Grignard reagent. These compounds were evaluated as glycosidase inhibitors and their potential as chaperones for mutant lysosomal galactosidases determined. Based on these results and on docking studies, the 5- C -pentyl derivative1 was selected as the optimal structure for further investigations: this compound induces the maturation of mutated β-galactosidase in fibroblasts of a GM1-gangliosidosis patient and promote the decrease of keratan sulfate and oligosaccharide load in patient cells. Compound1 is clearly capable of restoring β-galactosidase activity and of promoting maturation of the protein, which should result in significant clinical benefit. These properties strongly support the development of compound1 for the treatment of GM1-gangliosidosis and Morquio disease type B patients harboring β-galactosidase mutations sensitive to pharmacological chaperoning.